2016
DOI: 10.4103/0253-7613.178830
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonsteroidal anti-inflammatory drugs on colorectal distension-induced visceral pain

Abstract: Objectives:To investigate nonsteroidal anti-inflammatory drugs effectiveness in colorectal distension (CRD)-induced visceral pain model.Materials and Methods:Male Sprague–Dawley (250–300 g) rats were anesthetized with ketamine (50 mg/kg, intraperitoneally [i.p.]) and chlorpromazine (25 mg/kg, i.p.). Two bipolar Teflon-coated Ni/Cr wire electrodes (80-M diameter) were placed in the abdominal external oblique muscle for the recording of electromyography. Jugular vein catheter was placed for the administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Over the last two decades, the WHO GGP was widely reported as one of the cornerstones of prescribing education, and this is consistent with the findings of this review [10][11][12]. Thirty-five studies included in the current review aimed to improve prescribing skills, and six of these explicitly reported designing their educational interventions based on the WHO GGP six-step approach [20,36,53,64,80,89]. All six studies reported positive Kirkpatrick level 1 outcomes and four of these also reported positive Kirkpatrick level 2 findings [20,36,53,64].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Over the last two decades, the WHO GGP was widely reported as one of the cornerstones of prescribing education, and this is consistent with the findings of this review [10][11][12]. Thirty-five studies included in the current review aimed to improve prescribing skills, and six of these explicitly reported designing their educational interventions based on the WHO GGP six-step approach [20,36,53,64,80,89]. All six studies reported positive Kirkpatrick level 1 outcomes and four of these also reported positive Kirkpatrick level 2 findings [20,36,53,64].…”
Section: Discussionsupporting
confidence: 82%
“…Eleven studies used multicomponent interventions [42,52,53,67,71,[89][90][91][92][93][94], and of these, seven focused on prescribing skills and four on clinical pharmacology knowledge. Among all seven studies on prescribing skills, the most common components included prescription writing exercises (4 studies) [42,53,71,89], case-based learning (3 studies) [90,91,94], and group discussions (3 studies) [42,53,71].…”
Section: Multicomponent Educational Interventionsmentioning
confidence: 99%
See 1 more Smart Citation